3D‐Bioprinted Inflammation Modulating Polymer Scaffolds for Soft Tissue Repair. Issue 4 (16th December 2020) - Shin, Crystal S.; Cabrera, Fernando J.; Lee, Richard; Kim, John; Ammassam Veettil, Remya; Zaheer, Mahira; Adumbumkulath, Aparna; Mhatre, Kirti; Ajayan, Pulickel M.; Curley, Steven A.; Scott, Bradford G.; Acharya, Ghanashyam
Abstract: Development of inflammation modulating polymer scaffolds for soft tissue repair with minimal postsurgical complications is a compelling clinical need. However, the current standard of care soft tissue repair meshes for hernia repair is highly inflammatory and initiates a dysregulated inflammatory process causing visceral adhesions and postsurgical complications. Herein, the development of an inflammation modulating biomaterial scaffold (bioscaffold) for soft tissue repair is presented. The bioscaffold design is based on the idea that, if the excess proinflammatory cytokines are sequestered from the site of injury by the surgical implantation of a bioscaffold, the inflammatory response can be modulated, and the visceral adhesion formations and postsurgical complications can be minimized. The bioscaffold is fabricated by 3D‐bioprinting of an in situ phosphate crosslinked poly(vinyl alcohol) polymer. In vivo efficacy of the bioscaffold is evaluated in a rat ventral hernia model. In vivo proinflammatory cytokine expression analysis and histopathological analysis of the tissues have confirmed that the bioscaffold acts as an inflammation trap and captures the proinflammatory cytokines secreted at the implant site and effectively modulates the local inflammation without the need for exogenous anti‐inflammatory agents. The bioscaffold is very effective in inhibiting visceral adhesions formation and minimizing postsurgical complications. Abstract : An intrinsic inflammation modulating bioscaffold is developed by 3D‐bioprinting for surgical soft tissue repair. The bioscaffold is designed to sequester proinflammatory cytokines and acts as an inflammation trap. In vivo studies in a rat ventral hernia model demonstrate the enhanced efficacy of the bioscaffold by inhibiting formation of visceral adhesions and minimizing postsurgical complications.